Utilizing the AHSP Method for Cost Estimation in Road Improvement at Jalan Parit Demang - Oktaviani, Rizki; Lusiana, Lusiana; Rafie, Rafie (Jurnal Teknik Sipil, 2024)
Road infrastructure improvement is one of the important elements in supporting a country's economic development. Accurate cost estimation is key to road construction projects' success, ensuring efficient budgeting and resource allocation. This research uses data from interviews, observations, planning documents, and supporting literature sourced from official government websites. The method used is the Work Unit Price Analysis (AHSP) based on the Minister of PUPR Regulation No. 1 of 2022 to estimate the Cost Budget Plan (RAB) for the improvement project of Jalan Parit Demang. The results obtained show that the total project cost reached IDR 15,754,053,157. Meanwhile, the AHSP method provides a reliable framework for cost estimation; the analysis also emphasizes the importance of regular price data updates and contingency planning to anticipate market volatility. The research findings will improve budget estimation accuracy and resource efficiency in future infrastructure projects.